The sociology of global climate change. (12th November 2014) - Zehr, Stephen
Abstract : Sociological research on global climate change (GCC) can be found in several subfields, but it has primarily emerged within the theoretical and substantive domain of sociology of the environment. This review provides an overview of sociological literature on climate change and identifies key areas for further research and development. The review focuses on four broad areas: social causes, construction of the problem, relationship between GCC and social inequality, and social dimensions of mitigation and adaptation. WIREs Clim Change 2015, 6:129–150. doi: 10.1002/wcc.328 This article is categorized under: Social Status of Climate Change Knowledge > Sociology/Anthropology of Climate Knowledge